Civic Minstrels in Late Medieval England: New Light on Duties and Careers. Issue 1 (April 2021) - Rastall, Richard
Abstract: The publications of the ongoing Records of Early English Drama project since 1979 have made available for the first time much early documentation about minstrels, including the civic minstrels or town waits. While this material leaves many questions unanswered, a more detailed picture of the early history of civic minstrels is emerging. This article focusses on three aspects of that history that have not previously been studied as such: the towns that employed civic minstrels by 1509, the minstrels' possible special duties in ports, and their employment mobility.